Thoraco-abdominal Ganglioneuroma, Retroperitoneal. About a Case (International Journal of Medical and Surgical Sciences, 2015)
Ganglioneuroma (GN) is a benign infrequent tumor whose most common site is the abdomen. Theyare usually asymptomatic and usually diagnosed incidentally by imaging study. Treatment is surgical and indication for surgery depends on the size and location of the lesion; as well as the symptoms that are possibly generated. Even though there is evidence of laparoscopic resection in some cases of retroperitoneal location based on isolated cases reporting promising results, the main access road remains the traditional way. The aim of this article is to provide a case of thoracoabdominal retroperitoneal GN and discuss the related literature.